Studying the Magnetic Properties and Corrosion Resistance of Coated NdFeB Magnets - Fatih Doğan (Materials Proceedings)
Commercial NdFeB magnets are often coated with different thin layers to increase corrosion resistance. Fast and reliable test methods are being developed, especially for the automotive industry. Since corrosion test methods can inadequately describe the operating conditions of the e-motor, magnets are usually only tested in the demagnetized state. Corrosion tests close to sintered NdFeB magnet e-motor application conditions have been applied. Corrosion tests for sintered NdFeB magnets are usually demagnetized and performed in aqueous solutions or vapor environments instead of organic substances such as oil. In this study, sintered NdFeB magnets were immersed in a pre-saturated water-based salt solution and placed in gearbox oil. The test conditions have been specially selected to test the suitability of the magnets for e-motor applications (e.g., in hybrid vehicles). The microstructural effect of magnetic properties and corrosion resistance on the NdFeB magnets have been systematically studied. The aim of the study is the realization of the coating on the sintered NdFeB magnet, which provides high corrosion resistance and significantly reduces the thickness of the coating and ensures maximum efficiency in the use of magnets. The results of these studies are thought to play an important role in determining and optimizing the usage strategy of coated NdFeB magnets.